Evaluation of PK/PD Properties of Recommended Doses of Meropenem in Critically Ill Patients with Augmented Renal Clearance, A Prospective Observational Study: Meropenem Dosing in Augmented Renal Clearance - Nezarat, Fatemeh; Hassanpour, Rezvan; Kobarfard, Farzad; Pourheidar, Elham; Bahman, Reza; Sistanizad, Mohammad (Iranian Journal of Pharmaceutical Sciences, 2022)
Augmented renal clearance (ARC) is a common phenomenon among critically ill patients and creates sub-therapeutic concentrations of antibiotics, due to an increase in renal clearance of them. We evaluated the Pharmacokinetic and Pharmacodynamic (PK/PD) properties of recommended doses of meropenem in critically ill patients with ARC. Adult critically ill patients with confirmed ARC, based on 12-hour Creatinine Clearance (CrCl) (≥130 ml/min/1.73 m2), who received standard doses of meropenem enrolled in this study. Two blood samples were gathered from each participant, at the steady-state time, to determination of peak and trough concentrations. Serum concentrations of meropenem were measured by high-performance liquid chromatography (HPLC) with an ultra-violet (UV) detector. From eighteen paired samples (peak and trough concentrations) that were obtained from 16 critically ill patients, peak concentrations were significantly lower in group 1 (received meropenem 1g every 8 hours) than in group 2 (received meropenem 2g every 8 hours) (mean ±SD, 5.95 ±3.39 µg/mL vs. 11.93± 4.18 µg/mL, respectively, p=0.005). Trough concentrations were sub-threshold (< 2 µg/mL) in 10 patients of group 1 (83.3%) and 3 patients of group 2 (50%). ft > MIC ≥ 50% was achieved in 83.3% of patients in both groups whereas 16.6% of patients of group 1 and 33.3% of patients of group 2 had ft> MIC= 100%. Augmented renal clearance is an essential cause of sub-therapeutic concentrations of meropenem in critically ill patients, and higher than the recommended doses of meropenem administered as an intermittent infusion may be necessary to achieve the PD targets and improve efficacy.